1993
DOI: 10.1063/1.355265
|View full text |Cite
|
Sign up to set email alerts
|

Second-order optical nonlinearity in corona-poled glass films

Abstract: Several experiments were performed to elucidate the origin of the second-order optical nonlinearity χ(2) induced in the corona-poled Corning 7059 glass films. The values and the time decay of the second-harmonic coefficient d33 were measured for the glass films poled on several different kinds of substrates. The value of d33 was found to be dependent on the kinds of substrates. It was also observed that the glass films poled on a soda-lime substrate showed faster time decay of d33 than those poled on a Pyrex g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…One can notice the intensity remarkably increased by poling near glass transition temperature. This relationship agrees with the observation of tellurite glasses, 6 and thus it is indicated that the translational movement inside of the glasses plays important role of the origin of the second harmonic generation. The intensity decreased by the poling above glass transition temperature.…”
Section: Resultssupporting
confidence: 79%
“…One can notice the intensity remarkably increased by poling near glass transition temperature. This relationship agrees with the observation of tellurite glasses, 6 and thus it is indicated that the translational movement inside of the glasses plays important role of the origin of the second harmonic generation. The intensity decreased by the poling above glass transition temperature.…”
Section: Resultssupporting
confidence: 79%
“…Among the available poling techniques, thermal poling has proven to be both straightforward and reliable [1]. The v (2) in thermally poled silica is of the order of 1 pm/V, possesses excellent long-term stability at room temperature and is determined mainly by the poling conditions [1]. In practice, the level of v (2) does not change significantly with the chemical composition of the glass although the latter has a dramatic influence on the stability of v (2) [7].…”
Section: Introductionmentioning
confidence: 98%
“…Breaking of the symmetry, which can be achieved by various poling techniques [1][2][3][4][5], provides the glass with second-order non-linear optical susceptibility v (2) , which can be exploited in order to implement electro-optic and second-order non-linear effects in glass planar waveguides or optical fibres [6]. Among the available poling techniques, thermal poling has proven to be both straightforward and reliable [1].…”
Section: Introductionmentioning
confidence: 99%
“…The composition, room temperature resistivity, and refractive index of each glass are shown in Table 1 [14]. The refractive index of the Corning 7059 film was measured by the optical waveguide m-line method [16].…”
Section: Sample Preparation and Optical Propertiesmentioning
confidence: 99%
“…Nasu and colleagues proposed a model based on OH bonding in glass [10,11]. Apart from the reports on bulk glass [712], Okada and colleagues reported on phased-matched SHG (wavelength: 532 nm) in a glass thin film with corona poling [13] and qualitatively explained its origin as a glass interfacial effect [14]. We have also reported on the effect of the constituents (SiO 2 , B 2 O 3 , Al 2 O 3 , BaO) in a Corning 7059 glass film [15].…”
Section: Introductionmentioning
confidence: 98%